The benefits of GLP1 receptors in cardiovascular diseases - Ferhatbegović, Lamija; Mršić, Denis; Macić-Džanković, Amra (Frontiers in Clinical Diabetes and Healthcare, 2023)
Glucagon like peptide-1 (GLP-1) receptor agonists are well established drugs for the treatment of type 2 diabetes (T2D). In addition to glycemic control, GLP-1 receptor agonists have beneficial other effects. They act by binding to GLP-1 receptors, which are widely distributed in the body, including cardiomyocytes and blood vessels. The aim of this article is to provide a comprehensive review of GLP-1 receptor agonists impact on cardiovascular outcomes and risk reduction. In the last decade, several cardiovascular outcomes trials (CVOT) have been conducted in order to explore cardiovascular benefit of GLP-1 receptor agonists. CVOTs primarily proved cardiovascular safety and tolerability of different GLP-1 receptor agonists, but also showed cardiovascular benefit of specific drugs. CVOTs have shown that GLP-1 receptor agonists reduce MACE in patients with T2D compared to placebo. In addition, they have positive impact on several cardiovascular risk factors such as obesity by promoting weight loss, blood pressure and blood lipid levels. Also, they stimulate the endothelium to produce nitric oxide, reduce oxidative stress, and have antiatherogenic and antiinflammatory effects. Studies have shown their positive impact on kidney outcomes in patients with T2D compared to placebo. The results of previous trials are encouraging in terms of multiple positive effects of GLP-1 receptor agonists. However, further research is needed to understand their full potential and all details of their mechanism of action, which will enable to expand the therapeutic indications and to determine their optimal use in clinical practice.